COLONIZATION PREVALENCE AND SUSCEPTIBILITY OF Streptococcus agalactiae IN PREGNANT WOMEN AT HUSM - Veit, Adriane Regina; Roehrs, Magda Cristina Souza Marques; Mayer, Leticia Eichstaedt; Santos, Silvana Oliveira; Martini, Rosieli; Tizotti, Maísa Kräulich; Kempfer, Cláudia Barbisan; Martins, Vanessa Rodrigues; Fronza, Lisete; Cunha, Melissa Dias Costa; Colpo, Paola Roehrs; Konopka, Cristine Kolling; et al. (Saúde (Santa Maria), 2011)
ABSTRACT The Streptococcus agalactiae colonization prevalence and its susceptibility to antimicrobials in pregnant women at University Hospital of Santa Maria (HUSM) were evaluated from June to December 2009. The vaginal-rectal material was inoculated into tubes containing Todd-Hewitt broth with subsequent subculture on blood agar. The GBS identification was made through presumptive tests, confirmed by serological test and its susceptibility was evaluated. The occurrence of GBS maternal-fetal transmission in the colonized pregnant women was researched. The GBS colonization was 11.11%._All strains were susceptible to penicillin, ampicillin, and vancomycin. Two strains (50%) were intermediate to clindamycin and one (25%) intermediate to erythromycin._A newborn whose mother was colonized had early-onset neonatal infection by GBS. By this, it is very important the research about the colonization by GBS in all pregnant women from 35 to 37 weeks of gestation and the use of intrapartum antibiotic prophylaxis for colonized pregnant women. Descriptors: Streptococcus agalactiae; Prevalence; Pregnant women; Newborns; Microbial Sensitivity Tests. RESUMO Avaliou-se a prevalência de colonização pelo Streptococcus agalactiae e o seu perfil de sensibilidade frente aos antimicrobianos em gestantes no Hospital Universitário de Santa Maria (HUSM), de junho a dezembro de 2009. O material vaginal-retal foi inoculado em tubos contendo caldo Todd-Hewitt com posterior subcultura em ágar sangue. A identificação do EGB foi realizada através de testes presuntivos, confirmadas por teste sorológico e avaliado seu perfil de sensibilidade. Pesquisou-se ocorrência de transmissão materno-fetal do EGB nas gestantes colonizadas. A prevalência de colonização foi de 11,11%. Todas as cepas foram sensíveis à penicilina, ampicilina e vancomicina. Duas cepas (50%) foram intermediárias à clindamicina e uma (25%) intermediária à eritromicina. Um recém-nascido de mãe colonizada teve infecção neonatal de início precoce por EGB. Confirma-se a importância da pesquisa de colonização por EGB em todas as gestantes entre 35ª e 37ª semana de gestação e uso de quimioprofilaxia intraparto nas gestantes colonizadas. Descritores: Streptococcus agalactiae; Prevalência; Gestantes; Recém-nascido; Testes de Sensibilidade Microbiana.